Duodeno-cava fistula secondary to metallic foreign body and inferior cava vein thrombosis - Virgili, Agustín (2025)
Duodeno-caval fistula (DCF) is an extremely rare entity that can have potentially lethal consequences. It is associated with infectious, neoplastic, traumatic processes, or foreign bodies. We report a case of DCF secondary to the migration of a metallic wire from the duodenum to the inferior vena cava (IVC), accompanied by extensive venous thrombosis. A 48-year-old male with no relevant medical history presented with fever and nonspecific abdominal pain. He was admitted with an initial diagnosis of acute dengue in the context of an ongoing epidemic. Computed tomography revealed a linear metallic foreign body crossing the second portion of the duodenum, penetrating the visceral wall, and lodging within the lumen of the IVC, with air inside and extensive venous thrombosis. Upper digestive video endoscopy (EGD) was performed, with successful extraction of the foreign body. The patient received intravenous antibiotic therapy for 10 days and oral anticoagulation for 6 months. Clinical evolution was favorable, and the patient recovered without complications. DCF due to a foreign body is extremely rare. Endoscopic management can be successful in selected cases, avoiding invasive surgical procedures.